Four-Factor Prothrombin Complex Concentrate Reduces Time to Procedure in Vitamin K Antagonist-Treated Patients Experiencing Gastrointestinal Bleeding: A Post Hoc Analysis of Two Randomized Controlled Trials. (19th September 2017) - Refaai, Majed A.; Kothari, Truptesh H.; Straub, Shana; Falcon, Jacob; Sarode, Ravi; Goldstein, Joshua N.; Brainsky, Andres; Omert, Laurel; Lee, Martin L.; Milling, Truman J.
Abstract : Introduction . To investigate the impact of a 4-factor prothrombin complex concentrate (4F-PCC [Beriplex®/Kcentra®]) versus plasma on "time to procedure" in patients with acute/severe gastrointestinal bleeding requiring rapid vitamin K antagonist (VKA) reversal prior to invasive procedure. Methods . A post hoc analysis of two phase III trials of 4F-PCC versus plasma in patients with acute/severe gastrointestinal bleeding. The treatment arms were compared for study treatment volume, infusion times, and time from start of study treatment to procedure. Results . Analysis included 42 patients (plasma, n = 2 0 ; 4F-PCC, n = 22 ). Median (interquartile range) infusion time was significantly shorter for the 4F-PCC group than for the plasma group (16 [13, 26] min versus 210 [149, 393] min;P < 0.0001 ). Median infusion volumes were significantly smaller (103 [80, 130] mL versus 870 [748, 1001] mL;P < 0.0001 ) and median time from study treatment initiation to first procedure was significantly shorter in the 4F-PCC group than in the plasma group (17.5 [12.8, 22.8] versus 23.9 [18.5, 62.0] h;P = 0.037 ). Conclusions . In this analysis of patients with acute/severe gastrointestinal bleeding requiring urgent VKA reversal prior to an invasive procedure, 4F-PCC (compared with plasma) was associated with smaller infusion volumes, shorter infusion times, and reduced time to procedure.